2015
DOI: 10.1038/srep07617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Water-Soluble Polythiophene Derivatives for Cell Imaging

Abstract: In this work, four water-soluble polythiophene derivatives (PT, PT-DDA, PT-ADA, and PT-ADA-PPR) with different pendant moieties were synthesized via oxidative copolymerization by FeCl3. By increasing the hydrophobic ability of side chain moieties, there is a gradually blue shift for the maximum absorption wavelength and red shift for the maximum emission wavelength, a reducing trend for fluorescence quantum yields, a growing trend for Stokes shift, and an increasing trend for the mean sizes in the order of PT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
(50 reference statements)
2
33
0
Order By: Relevance
“…The above result suggests that WSPTs exhibit lower cytotoxicity than metal/semiconducting quantum dots and organic fluorescent dyes (Fig. ) . The low cytotoxicity and good photostability of WSPTs make them a better choice for lysosome‐specific imaging materials and localization.…”
Section: Water‐soluble Cptmentioning
confidence: 86%
See 2 more Smart Citations
“…The above result suggests that WSPTs exhibit lower cytotoxicity than metal/semiconducting quantum dots and organic fluorescent dyes (Fig. ) . The low cytotoxicity and good photostability of WSPTs make them a better choice for lysosome‐specific imaging materials and localization.…”
Section: Water‐soluble Cptmentioning
confidence: 86%
“…More recently, Wang et al have reported various water‐soluble CPT derivatives (WSPTs) such as PT, PT‐DDA, PT‐ADA and PT‐ADA‐PPR for cell imaging (Fig. ) …”
Section: Water‐soluble Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…All organic solvents and anhydrous ferric chloride were bought from Sinopharm Chemical Reagent Beijing Co., Ltd. Monomer 1, 2 and PPR were prepared referring to reported synthetic methods. 35,36 MTT (methylthiazolyldiphenyl-tetrazolium bromide) and FBS (fetal bovine serum) were bought from Xinjingke Biotechnology Co., Ltd (Beijing, China). DMEM (Dulbecco's modied Eagle medium) used to culture cells was purchased from HyClone/Thermosher.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…The optical and electronic interplay of these molecular moieties is, however, more widely being taken advantage of in the field of optoelectronics and photovoltaics. 122,123 Examples of polymeric thiophene-porphyrin conjugates and complexes can be found in literature, where the interactions of these structural moieties give rise to optical readouts for detecting bacteria 124 and eukaryotic cells 125 , or where such compounds are used for photodynamic inactivation of bacteria 126 and fungi 127 .…”
Section: Oligothiophene Porphyrin Hybrids As Fluorescent Probesmentioning
confidence: 99%